2013
DOI: 10.1002/aic.14092
|View full text |Cite
|
Sign up to set email alerts
|

Reactive coupling between immiscible polymer chains: Acceleration by compressive flow

Abstract: It is demonstrated that processing flow affects the kinetics of the interfacial coupling reaction between functional groups that are grafted to polymer chains. At melt temperatures the amine group on the end of nylon 6 chains reacts with maleic anhydride grafted polyethylene (PE‐MA) and forms graft copolymers. Bilayers were made by lamination and coextrusion and adhesion was measured using asymmetric dual cantilever beam (ADCB). The amount of graft copolymer in the interface was quantified by X‐ray photon spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Recently, basing on incompatible functional polymers, Song et al demonstrated that the extensional and compressive flow in coextrusion overcomes the diffusion barriers by decreasing the diffusion length scale, thus enhances diffusive flux of local reactive functions and eventually contributes to the accelerated reaction rate during coextrusion. Change of the diffusion lengthscale or diffusion layer after being subjected to the external flow could be appraised from a theoretical viewpoint.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, basing on incompatible functional polymers, Song et al demonstrated that the extensional and compressive flow in coextrusion overcomes the diffusion barriers by decreasing the diffusion length scale, thus enhances diffusive flux of local reactive functions and eventually contributes to the accelerated reaction rate during coextrusion. Change of the diffusion lengthscale or diffusion layer after being subjected to the external flow could be appraised from a theoretical viewpoint.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [111] showed experimentally that the presence of an external flow accelerates interfacial reactions. Song et al [112] also showed an acceleration of the reaction under a compressive flow, and state that this explains the remarkable ability of co-extrusive processes to build multilayer products with little residence times. These more realistic experimental conditions are still missing in the theories of kinetic evolution of copolymer coverage of the interface.…”
Section: Reaction-limited Systemsmentioning
confidence: 90%
“…The silane coupling agents condensate after manufacturing and generate bonding across the interface. The idea is similar to placing a reactive inside different thermoplastics to improve adhesion 25 27 . Our approach improves adhesion independent of the sequence of forming the networks, and enables various manufacturing processes difficult or impossible to achieve using existing approaches.…”
Section: Introductionmentioning
confidence: 99%